2018
DOI: 10.1007/s10909-018-2006-0
|View full text |Cite
|
Sign up to set email alerts
|

Josephson Effects in Frequency-Domain Multiplexed TES Microcalorimeters and Bolometers

Abstract: Josephson Effects in Frequency-Domain Multiplexed TES Microcalorimeters and Bolometers Gottardi, L.; Smith, S. J.; Kozorezov, A.; Akamatsu, H.; Bruijn, M. P.; Chervenak, J. A.; Gao, J. R.; Jackson, B. D.; Ridder, M.; More AuthorsAbstract Frequency-division multiplexing is the baseline read-out system for large arrays of superconducting transition-edge sensors (TES's) under development for the X-ray and infrared instruments like X-IFU (Athena) and SAFARI, respectively. In this multiplexing scheme, the sensors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
(23 reference statements)
1
19
0
Order By: Relevance
“…The high frequency pixels are characterized by strongly fluctuation values of α and β , especially for low values of R/R n . The oscillations are caused by the weak-link effect 19,20 . The low frequency pixels are less affected by this problem.…”
Section: B Complex Impedancementioning
confidence: 99%
See 1 more Smart Citation
“…The high frequency pixels are characterized by strongly fluctuation values of α and β , especially for low values of R/R n . The oscillations are caused by the weak-link effect 19,20 . The low frequency pixels are less affected by this problem.…”
Section: B Complex Impedancementioning
confidence: 99%
“…Here k B is Boltzmann's constant and M 2 is the excess noise, given by the difference between the measured and predicted noise. This excess noise is typically explained by other noise sources, such as the weak-link effect described by the resistively shunted junction (RSJ) model 20,45 , the presence of phase-slip lines 46 , or ITFN 11,15,[47][48][49] . In this paper, we will not go into a detailed analysis of the origin of the excess noise, but instead use it as a guideline to find the optimal TES design.…”
Section: Excess Noisementioning
confidence: 99%
“…At the low bias frequency, for the first time, we have archived DC bias compatible performance under AC bias 13,14 . At higher frequency, there is a slight degradation which can be impacts of AC loss 15 , AC Josephson effect 16 and contributions from the room temperature electronics. Both performances are better than predictions from the integrated noise equivalent power (NEP).…”
Section: Performance Under Single Pixel Mode and Multiplexing Experimentsmentioning
confidence: 99%
“…In the past few years, an extensive research collaboration on this issue has been made between NASA/Goddard and SRON. As outcomes, two types of frequency-dependent physical effects, namely AC losses and the Josephson effect, have been identified and theoretical analyses have shown that both effects can be mitigated by increasing the total TES normal resistance [4,5]. This is possible by decreasing the TES thickness however, it seems also important to have a thick TES film for a better thermal conductivity.…”
Section: K Nagayoshi • ML Ridder • Mp Bruijn • L Gottardi • E mentioning
confidence: 99%